Training On Budget Preparation And Selling Price Determination For Micro Beverage Yoghurt Business - Prihastuti, Asepma Hygi; Wahyuni, Sri; Adriyani, Annesa; Ramadhani, Suci; Zainal, Rahmi (Pasundan Community Service Development, 2024)
This training on preparing budgets and determining selling prices for yoghurt drink micro businesses was motivated by the fact that many yoghurt micro businesses still experience difficulties in preparing budgets and determining product selling prices. Several factors that cause this, include a lack of knowledge about cost analysis, understanding of the market, and appropriate pricing strategies. Without these skills, business owners could face the risk of loss, and could even fail in running their business, even though demand for ready-to-eat food and beverage products such as yoghurt continues to increase. This market offers great opportunities for micro businesses who want to offer innovative products that meet consumer demand as well as the large amount of government support for micro businesses in various government programs. And many consumers prefer local products that are more homemade and natural, and believe that these products have better quality. This training has provided an in-depth and practical understanding of the importance of financial management in running a business. The following are important points that are the conclusions of this training, namely: 1) The importance of preparing a budget; 2) Calculation of production costs; 3) Selling price determination strategy; 4) Market analysis; 5) Financial management; and 6) Improving practical skills for mothers of West Labuh Baru Village in Pekanbaru.